Are consumers willing to pay more for biofortified foods? Evidence from a field experiment in Uganda - Chowdhury, Shyamal; Meenakshi, Jonnalagadda V.; Tomlins, Keith; Owori, Constance (International Food Policy Research Institute, 2009)
This paper attempts to address this question by using a choice experiment with the real product to quantify the magnitude of the premium or discount in consumers’ willingness to pay that may be associated with it. It also considers the extent to which the provision of nutrition information affects valuations. Finally, the paper addresses whether the use of hypothetical scenarios is justified in a developing country context, and quantifies the magnitude of hypothetical bias that results as a consequence.